Formulation and Evaluation of Nail Drug Delivery System of Anti Fungal Drug - Nikhath, Misbah; S, Sanjana (Asian Journal of Pharmaceutical Research and Development, 2022)
The purpose of this study was to prepare nail lacquer for nail drug delivery system of anti fungal drug in order to improve the physicochemical parameters that influence the drug permeation through a nail plate to reach the systemic circulation and the neighbouring target sites. The success of local topical therapy for onychomycosis depends on the achievement of effective chemical concentrations into/through the human nail plate; therefore, a suitable antifungal drug must be coupled with an appropriate delivery method. The method should maximize the effect of the active principle by aiding its diffusion into the nail bed to levels exceeding the minimum inhibitory concentration (MIC) against local infection by dermatophytes. Thus, a suitable carrier may be needed to enhance drug penetration through the nail barrier. The nail lacquer formulations were prepared by simple mixing method and analyzed for non volatile content, gloss, smoothness to flow, drug diffusion studies, and % drug content. Among all formulations, nail lacquer prepared with 2% oxiconazole, 6% nitrocellulose, 1% ethyl cellulose, 15% salicylic acid, 10% propylene glycol and 10% 2-H β-CD exhibited good non volatile content, drug release, drug content estimation and zone inhibition i.e. F4 formulation. The drug release profiles were achieved 93.2% at 12 h. The in vitro ungual permeation studies revealed a good in vitro in vivo correlation. Nail lacquer were substantially stable after 1 month storage at 40±2℃.